Hubungan mean platelet volume dengan miocardial blush kuantitatif pada pasien ima-est yang menjalani intervensi koroner perkutan primer - Sri Murdiati; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2013)
Background. Mean platelet volume is a marker of platelet, size and activation functions. Increased mean platelet volume showed a large and active platelet release more thromboxane A2 than smaller ones. A simple marker was detected using a fast and functional techniques will help approaches to inflammation caused by platelets. Thus MPV is an important examination of effective simple, easy, and low cost to be used and explored extensively, particularly in developing countries such as Indonesia, to predict the likelihood of complications to come.Methods and Results. Seventy-two patients (age minimum 30 years and maximum 80 years who came to the hospital with a presentation IMA-EST onset less than 12 hours were included in this study. Following primary percutaneous intervention coroner examined myocardial blush with Qube and see the relationship with the value mean platelet volume (MPV) in assessing myocardial flow. End point of this study is the lack of correlation between MPV values in the assessment of myocardial blush Qube post-reperfusion.Conclusion. MPV values in this population as the initial entry no relationship with Qube in assessing the value of post-reperfusion myocardial blush